2011
DOI: 10.1007/s12598-011-0211-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ho on the microstructure and mechanical properties of Mg-Zn-Ho-Zr magnesium alloys

Abstract: The microstructure and mechanical properties of Mg-Zn-Ho-Zr alloys have been investigated in detail. The grain size of the as-cast Mg-Zn-Ho-Zr alloy was greatly decreased by the addition of Ho, and the grain growth during solution treatment was suppressed by Mg-Zn-Ho phases formed at grain boundaries. These thermally stable Mg-Zn-Ho phases could not completely dissolve into the matrix during solution treatment, and the strengthening effect of solution-plus-ageing treatment weakened. The addition of Ho can grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…In this study, the Mg-Ho phases were identified as MgHo 3 and Mg 2 Ho, which differs from the reported Mg-Zn-Ho phases 15 and the Mg 24 Ho 5 phase along the grain boundaries 36 . An isolation between Sr and the Mg matrix was introduced with the increased addition of Ho (EDX mapping, Fig.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In this study, the Mg-Ho phases were identified as MgHo 3 and Mg 2 Ho, which differs from the reported Mg-Zn-Ho phases 15 and the Mg 24 Ho 5 phase along the grain boundaries 36 . An isolation between Sr and the Mg matrix was introduced with the increased addition of Ho (EDX mapping, Fig.…”
Section: Discussioncontrasting
confidence: 92%
“…Among REEs, Ho (>0.5 wt. % hereafter) has been used to enhance the tensile properties of Mg-Zn-Al due to the reduction of the petal-like phase 14 and Ho also displays potential effects on grain refinement, resulting in significant improvement in strength and plasticity 15 . However, in view of the performance of Ho in relation to biocompatibility, a limited number of studies made comparisons under identical experimental conditions 16 17 .…”
mentioning
confidence: 99%
“…It can be revealed that holmium acts as a grain refiner to this alloy. Li et al [17] found that the addition of 2.0 wt.% Ho has a great refinement effect on Mg-Zn-Zr alloys compared to the base alloys. This finding is also supported by Le et al [19].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have been reported that holmium additions are mainly attributed to the precipitation of the β′-Mg 15 RE 3 (Gd/Ho) metastable phase [16]. The others researcher also announced that by adding the holmium into the magnesium alloy leads to the high ultimate tensile strength and also played an important role in grain refinement effect [17].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc additions improve mechanical and corrosion performance while reducing hydrogen evolution. However, at high concentrations (≥5%), Zn leads to poor corrosion resistance and mechanical strength, including reduced biocompatibility [6][7][8][9][10][11][12][13][14][15]23,61,63,64].…”
Section: Mg Alloying Systemsmentioning
confidence: 99%